2011
DOI: 10.1002/bit.23022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of shear stress experienced by endothelial cells cultured on microstructured polymer substrates in a parallel plate flow chamber

Abstract: The application of physical stimuli to cell populations in tissue engineering and regenerative medicine may facilitate significant scientific and clinical advances. However, for the most part, these stimuli are evaluated in isolation, rather than in combination. This study was designed to combine two physical stimuli. The first being a microstructured tissue culture polystyrene substrate, known to produce changes in cell shape and orientation, and the second being laminar shear stress in a parallel plate flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…These studies did not examine the effect of surface topography on gene expression. Other studies have investigated micropillar surface protrusions but only in static culture or under short (1 h) flow conditions . In a study of ECs on surfaces with ordered holes, Morgan et al found that surfaces with holes of various dimensions up to 4 μm pitch did not significantly change the extent of EC or nucleus realignment to flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies did not examine the effect of surface topography on gene expression. Other studies have investigated micropillar surface protrusions but only in static culture or under short (1 h) flow conditions . In a study of ECs on surfaces with ordered holes, Morgan et al found that surfaces with holes of various dimensions up to 4 μm pitch did not significantly change the extent of EC or nucleus realignment to flow.…”
Section: Discussionmentioning
confidence: 99%
“…Liliensiek et al showed that flow primarily determined orientation of ECs adherent on closely spaced (400–800 nm) polyurethane ridges but that surface topography had a greater influence on orientation for larger feature spaces (2000–4000 nm). When fluid shear stress is applied, endothelial cells align and elongate in the direction of flow, which is enhanced if the surface is endowed with long grooves or ridges along the same direction . Likewise, endothelial nuclei align along the direction of grooves, when flow is applied in the same direction as the surface grooves .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…were solved simultaneously to compute the flow field within the flow chamber : ρ|u.u=.[]|p+μ|u+ρg ρ.false(ufalse)=0 where u is the local velocity, μ is the fluid dynamic viscosity, p is the fluid pressure, and g is the gravity constant. The fluid inlet velocity boundary condition is given as : u|normalz=6 Vnormalm (truezH)(1 truezH) where V m is the averaged input velocity, z is the direction normal to the flow direction, and H is the height of the parallel‐plate flow chamber. The inlet flow was considered to be nonoscillatory which is consistent with the pump characteristics used in the experiments.…”
Section: Methodsmentioning
confidence: 99%